The novel compound heterozygous rare variants may impact positively selected regions of TUBGCP6, a microcephaly associated gene - Chen, Jianhai; Ying, Lijuan; Zeng, Li; Li, Chunyu; Jia, Yangying; Yang, Hao; Yang, Guang (Frontiers in Ecology and Evolution, 2022)
The microcephaly is a rare and severe disease probably under purifying selection due to the reduction of human brain-size. In contrast, the brain-size enlargement is most probably driven by positive selection, in light of this critical phenotypical innovation during primates and human evolution. Thus, microcephaly-related genes were extensively studied for signals of positive selection. However, whether the pathogenic variants of microcephaly-related genes could affect the regions of positive selection is still unclear. Here, we identified novel compound heterozygous variants, p.Y613* and p.E1368K in TUBGCP6, related to microcephaly in a Chinese family. The genotyping and the sanger sequencing revealed the maternal and the paternal origin for the first and second variant, respectively. The p.Y613* occurred before the second and third domain of TUBGCP6 protein, while p.E1368K located within the linker region of the second and third domain. Interestingly, using multiple positive selection analyses, we revealed the potential impacts of these variants on the regions of positive selection of TUBGCP6. The truncating variant p.Y613* could lead to the deletions of two positively selected domains DUF5401 and Spc97_Spc98, while p.E1368K could impose a rare mutation burden on the linker region between these two domains. Our investigation expands the list of candidate pathogenic variants of TUBGCP6 that may cause microcephaly. Moreover, the study provides insights into the potential pathogenic effects of variants that truncate or distribute within the positively selected regions.